Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/mnras/stw1468
|View full text |Cite
|
Sign up to set email alerts
|

Soft γ-ray selected radio galaxies: favouring giant size discovery

Abstract: Using the recent INTEGRAL/IBIS and Swift/BAT surveys we have extracted a sample of 64 confirmed plus 3 candidate radio galaxies selected in the soft gamma-ray band. The sample covers all optical classes and is dominated by objects showing a FR II radio morphology; a large fraction (70%) of the sample is made of "radiative mode" or High Excitation Radio Galaxies (HERG). We have measured the source size on NVSS, FIRST and SUMSS images and have compared our findings with data in the literature obtaining a good ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 70 publications
7
70
1
1
Order By: Relevance
“…The 15 GRG subject of this work have been extracted from a parent sample of 64 radio galaxies selected via cross-correlation of hard X-ray catalogues and radio surveys. Indeed, Bassani et al (2016) produced a catalogue of radio galaxies detected by the IN-TEGRAL/IBIS (Imager on Board the INTEGRAL Satellite) and/or Swift/BAT (Burst Alert Telescope), at energies >20 keV, identified using the two complementary radio surveys covering the whole sky: the NRAO Very Large Array Sky Survey (NVSS, 1.4 GHz, Condon et al 1998), and the Sydney University Molonglo Sky Survey (SUMSS, 843 MHz, Bock et al 1999). The same authors found that ∼25% of the objects in that sample have a projected linear size >0.7 Mpc, and can then be considered GRG (see Tab.…”
Section: The Hard X-ray Selected Grg Samplementioning
confidence: 99%
See 2 more Smart Citations
“…The 15 GRG subject of this work have been extracted from a parent sample of 64 radio galaxies selected via cross-correlation of hard X-ray catalogues and radio surveys. Indeed, Bassani et al (2016) produced a catalogue of radio galaxies detected by the IN-TEGRAL/IBIS (Imager on Board the INTEGRAL Satellite) and/or Swift/BAT (Burst Alert Telescope), at energies >20 keV, identified using the two complementary radio surveys covering the whole sky: the NRAO Very Large Array Sky Survey (NVSS, 1.4 GHz, Condon et al 1998), and the Sydney University Molonglo Sky Survey (SUMSS, 843 MHz, Bock et al 1999). The same authors found that ∼25% of the objects in that sample have a projected linear size >0.7 Mpc, and can then be considered GRG (see Tab.…”
Section: The Hard X-ray Selected Grg Samplementioning
confidence: 99%
“…In particular, LOFAR could provide at the same time high-sensitivity and high-resolution images of these GRG, making it possible to identify diffuse, low surface brightness emission. This work, presenting the morphology of the GRG sample from Bassani et al (2016), is the third in a series after Ursini et al (2018) and Bruni et al (2019) aiming at characterizing the combined X-ray and radio properties of the first GRG sample selected from INTE-GRAL/IBIS and Swift/BAT hard X-ray catalogues (>20 keV). Bassani et al (2016), who presented the parent sample of these GRG, found that this way of selecting radio galaxies favours large-sized objects, since ∼60% of their sample of radio galaxies emitting at hard X-rays has a size larger than 0.4 Mpc, and the fraction of GRG (22%) is about four times larger than what seen in radio surveys to date (∼6%, Ishwara-Chandra & Saikia 1999).…”
Section: Radio Cocoonmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the recent investigations of Bassani et al (2016) show that a large fraction of soft gamma-ray selected radio sources become GRSs. The all-sky observations of the INTErnational Gamma-Ray Astrophysics Laboratory (IN-TEGRAL;Winkler 1994) and Swift (Gehrels et al 2004) satellites reveal a large population of AGNs.…”
Section: Introductionmentioning
confidence: 99%
“…We measured a linear size of 1.2 Mpc (1125 arcsec from lobe to lobe, at a spatial scale of 1.087 kpc/arcsec) so it falls in the GRG category. Indeed, it is included in the recently-published sample of GRG selected in the soft gamma-ray band by Bassani et al (2016), and classified as an FRII. The symmetric structure has a position angle of about 45 degrees, with the southern jet less extended than the Northern one, which could be due to a projection effect.…”
Section: Radiomentioning
confidence: 99%